Effects of Digital Marketing and Branding Elements on Skincare Buying Decisions - Salsabila, Raihan; Firdausiah, RR Ayu (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth, leading to intense competition among local brands. As a result, companies must understand the factors that influence consumer behavior, particularly in purchasing decisions. This study aims to investigate the impact of digital marketing, brand image, and brand preference on the purchasing decisions of Generation Z for Avoskin skincare products. The population in this study consists of individuals born between 1997 and 2012 (Generation Z) who reside in Indonesia and use Avoskin skincare products. Data for this quantitative study were collected through an online survey of 150 respondents selected using purposive sampling based on those criteria. Multiple linear regression analysis using IBM SPSS 24 reveals that digital marketing, brand image, and brand preference each have a significant influence on buying decisions, both simultaneously and partially. These findings underscore the significance of digital communication strategies and effective brand image development in shaping preferences and influencing buying decisions among consumers, particularly those in digitally native age groups such as Generation Z.